Problematika KDRT dan Kesehatan Mental Anak: Mengatasi Trauma Masa Kecil untuk Masa Depan yang Lebih Baik - Tristina, Nadya Dewi (Maliki Interdisciplinary Journal, 2025)
Domestic violence has a significant impact on children’s mental health, both directly and indirectly. Children who witness or experience domestic violence are at high risk of experiencing emotional disorders, such as anxiety, depression, and PTSD. This trauma can disrupt their psychological development, causing behavioral problems, difficulties in social relationships, and reduced academic performance. Addressing childhood trauma through emotional support, psychological therapy, and creating a safe environment is critical to helping children recover and build a better future. The impact of childhood trauma can affect their psychological development and social life in the future. Therefore, efforts to prevent and address the impact of domestic violence on children’s mental health are very important. By providing the right support, access to therapy, and a safe environment, we can help these children overcome their trauma and build a better future